Electrode slurry, electrode, preparation method of electrode and battery
By adding fibrous polymer materials to the electrode slurry of the lithium-ion battery electrode sheet and controlling its thermal decomposition temperature and baking temperature, the problem of low effective porosity of the electrode sheet is solved, and the electrochemical performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411929710.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The effective porosity of existing lithium-ion battery poles is low, resulting in increased resistance and deterioration of magnification and cycling performance.
Fibrous polymer material is added to the electrode slurry, and the thermal decomposition temperature and baking temperature of the fibers are controlled through a specific baking and rolling process to increase the pore rate of the electrode sheet.
By increasing the pore rate of the electrode sheet, the liquid retention volume and ion diffusion efficiency of the electrolyte are enhanced, and the electrochemical performance of the battery is improved.
Smart Images

Figure CN119742313A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to an electrode slurry, an electrode and a preparation method thereof, and a battery. Background Art
[0002] Consumers are increasingly demanding higher energy density for battery products, and the thickness of lithium-ion battery pole pieces is also increasing. The increase in electrode thickness can significantly increase the proportion of active materials, but it can also cause problems such as increased pole piece tortuosity, increased resistance, and deterioration of rate and cycle performance. Hole-making in thick pole pieces can effectively solve this problem.
[0003] Currently, the common thick electrode pore-making technologies are mainly pore-forming agent pore-making and laser pore-making. Traditional pore-forming agents are gas-generating compounds that form channels when coated and dried, but will still form closed pores during the subsequent rolling process, and the pore-opening efficiency is low. Laser pore-making uses high-energy lasers to ablate the electrode coating at high temperatures to form pores, but there are problems such as high laser energy consumption, slow pore-making speed, high dust from molten beads, and easy failure of the coating in the pore-making area. Summary of the invention
[0004] The main purpose of the present application is to provide an electrode slurry, an electrode and a preparation method thereof, and a battery to solve the problem of low effective porosity of electrode sheets in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present application, an electrode slurry is provided, the electrode slurry includes an active material, a binder and a conductive agent; a fibrous polymer material is further added to the electrode slurry; the thermal decomposition temperature T of the fibrous polymer material, the baking temperature T1 of the electrode sheet coated with the electrode slurry before rolling, and the baking temperature T2 after rolling satisfy the following relationship:
[0006] T1<T≤T2.
[0007] Further, T1+10°C≤T≤T2.
[0008] Further, T1+20°C≤T≤T2.
[0009] Further, T1+30°C≤T≤T2.
[0010] Furthermore, T1 is 100-130°C.
[0011] Furthermore, T1 is 110-130°C.
[0012] Furthermore, T is 120-160°C.
[0013] Furthermore, T is 130-160°C.
[0014] Furthermore, T is 140-160°C.
[0015] Further, T2 is 150-165°C;
[0016] Furthermore, T2 is 160-165°C.
[0017] Furthermore, the fibrous polymer material is wool fiber and / or polyvinyl chloride fiber.
[0018] Furthermore, the ratio of the fiber length of the fibrous polymer material to the thickness of the active coating of the pole piece is (0.5-1.2):1.
[0019] Furthermore, the molecular weight of the fibrous polymer material is 4W to 6W g / mol.
[0020] Furthermore, the thickness of the active material layer of the pole piece is 60-85 μm.
[0021] Furthermore, the fiber length of the fibrous polymer material is 40 to 100 μm.
[0022] Furthermore, the fiber length of the fibrous polymer material is 60 to 90 μm.
[0023] Furthermore, the fiber diameter of the fibrous polymer material is 60 to 140 μm.
[0024] Furthermore, the fiber diameter of the fibrous polymer material is 100 to 120 μm.
[0025] Furthermore, the weight proportion of the fibrous polymer material in the electrode slurry is 0.5% to 5%.
[0026] Furthermore, the weight proportion of the fibrous polymer material in the electrode slurry is 1% to 4%.
[0027] Furthermore, the weight proportion of the fibrous polymer material in the electrode slurry is 1% to 3%.
[0028] Furthermore, the weight proportion of the fibrous polymer material in the electrode slurry is 1% to 2%.
[0029] Furthermore, the weight proportion of the active material in the electrode slurry is 93% to 97%; the weight proportion of the binder in the electrode slurry is 1% to 1.5%; and the weight proportion of the conductive agent in the electrode slurry is 1% to 1.5%.
[0030] Furthermore, the electrode is a positive electrode or a negative electrode.
[0031] Furthermore, the active material is a positive electrode active material or a negative electrode active material.
[0032] Furthermore, the positive electrode active material is selected from lithium cobalt oxide or ternary materials.
[0033] Furthermore, the negative electrode active material is selected from graphite.
[0034] Furthermore, the conductive agent is selected from conductive carbon black and / or carbon nanotubes.
[0035] Furthermore, the binder is selected from polyvinylidene fluoride.
[0036] According to a second aspect of the present application, a method for preparing an electrode is provided, the method comprising: coating an electrode slurry on a surface of a current collector, and sequentially performing a first baking, rolling and a second baking to obtain an electrode.
[0037] Furthermore, the temperature of the first baking is 100°C to 130°C.
[0038] Furthermore, the temperature of the first baking is 110°C to 130°C.
[0039] Furthermore, the temperature of the second baking is 150°C to 165°C.
[0040] Furthermore, the temperature of the second baking is 160°C to 165°C.
[0041] Furthermore, the first baking time is 1 to 2 hours.
[0042] Furthermore, the second baking time is 6 to 10 hours.
[0043] Furthermore, the rolling pressure speed is 10 to 20 m / min.
[0044] Furthermore, the mixing process of the electrode slurry includes: mixing the active material, the conductive agent, the binder and the solvent, adding the fibrous polymer material, mixing and stirring to obtain the electrode slurry.
[0045] Furthermore, the stirring time is 3 to 5 hours.
[0046] According to a third aspect of the present application, an electrode is provided, which is prepared using the above-mentioned preparation method.
[0047] Furthermore, the electrode is a positive electrode sheet or a negative electrode sheet; the surface density of the positive electrode sheet is 110-120 g / m 2 ; The surface density of the negative electrode is 60-70g / m 2 .
[0048] According to a fourth aspect of the present application, a battery is provided, comprising the above-mentioned electrode.
[0049] By applying the technical solution of the present application, an electrode slurry, an electrode and a preparation method thereof, and a battery are provided. In the present application, a small amount of thermally decomposable fibrous polymer material is added during the homogenization process, and no additional pore-forming equipment and pore-forming agent are used. The process is simple and easy to operate, and the proportion of through holes in the porosity of the electrode sheet can be increased. The through holes can improve the electrical properties of lithium-ion batteries, such as rate charge and discharge performance, cycle performance, etc. The pore-forming method used in the present application will not damage the electrode structure and will not cause structural failure in the pore-forming area. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0051] Figure 1 It shows a schematic diagram of the structure of the electrode sheet before baking and decomposition in Example 1 of the present application;
[0052] Figure 2 A schematic diagram of the structure of the electrode sheet after baking and decomposition in Example 1 of the present application is shown.
[0053] Reference numerals:
[0054] 1-Fiber-like polymer materials;
[0055] 2-Hole. DETAILED DESCRIPTION
[0056] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0057] In the existing technology, thick electrode pore-forming technology mainly adopts pore-forming agent pore-forming and laser pore-forming. The traditional pore-forming agent is a gas-generating compound, which has formed pores during coating and drying. However, in the subsequent rolling process, the rolling pressure will destroy some pores and form closed pores, resulting in low pore opening efficiency.
[0058] In order to solve the above-mentioned problem of low effective porosity, the present application has adopted a new idea to create pores in the electrode after extensive research; the effect of improving the effective porosity is achieved by improving the electrode slurry.
[0059] In order to achieve the above object, according to one aspect of the present application, an electrode slurry is provided, the electrode slurry includes an active material, a binder and a conductive agent; a fibrous polymer material is further added to the electrode slurry; the thermal decomposition temperature T of the fibrous polymer material, the baking temperature T1 of the electrode sheet coated with the electrode slurry before rolling, and the baking temperature T2 after rolling satisfy the following relationship:
[0060] T1<T≤T2.
[0061] The present application adds a fibrous polymer material with a specific pyrolysis temperature to the electrode slurry. When the electrode slurry is coated and baked, the thermal decomposition temperature of the fibers is higher than the baking temperature of the electrode sheet before rolling, so that a large number of specific fibers will not undergo thermal decomposition during the baking process before rolling. At this time, the specific fibers occupy a certain solid volume during the baking process and do not form a large number of pores. After the baked electrode sheet is rolled, since a large number of pores have not yet been formed, the rolling process will not affect the pores of the baked electrode sheet; and the thermal decomposition temperature of the specific fibers is lower than the baking temperature of the electrode sheet after rolling, so that a large number of fibers will undergo thermal decomposition and generate gas and escape during the baking process after rolling, so the electrode sheet can generate a large number of pores during the baking process. Through research, the present application discovered that the electrode sheet needs to be coated, dried, rolled, and baked in sequence to form the final rolled electrode sheet. The sequence of baking first, rolling later, and finally baking again is cleverly utilized. By screening fibers with a specific thermal decomposition temperature and the fibers being able to generate gas to form a certain volume of space after thermal decomposition, it is achieved that the specific fibers do not decompose during the baking process before rolling, and no pore structure can be destroyed during rolling. A large amount of thermal decomposition is performed during the baking process after rolling, and the pores generated by the thermal decomposition of the fibers are basically retained, thereby avoiding the phenomenon that the rolling process will destroy the pore structure in the active coating. This method increases the effective pore rate in the electrode sheet, and the increase in porosity can increase the liquid retention capacity of the electrolyte, improve the ion diffusion efficiency, and is beneficial to the improvement of electrochemical performance.
[0062] In some embodiments, T1+10°C≤T≤T2; further, T1+20°C≤T≤T2; further, T1+30°C≤T≤T2.
[0063] In some embodiments, T1 is 100-130°C; T is greater than or equal to 130°C and less than or equal to T2; further T1 is 110-130°C; for example, T1 is 100°C; T is 120-160°C; further T is 130-160°C; further T is 140-150°C; for example, T is 130°C; T2 is 150-160°C; further T2 is 155-160°C; for example, T2 is 150°C. For another example, the thermal decomposition temperature T of the fiber is any value among 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, or a range between any two of them; T1 is any value among 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, or a range between any two of them; T2 is any value among 150°C, 155°C, 160°C, or a range between any two of them.
[0064] The present application selects the fibers with the above-mentioned thermal decomposition temperature to match the appropriate baking temperature before and after rolling, which can minimize the thermal decomposition rate of the fibers during the baking process before rolling, and try to make all the fibers thermally decompose again during the baking process after rolling. When the thermal decomposition temperature of the fibers is too high, although the thermal decomposition rate can be further reduced during the baking process before rolling, the thermal decomposition temperature may be too high or higher than the post-baking temperature, which makes the thermal decomposition rate of the fibers in the baking process after rolling lower, thereby reducing the pore formation rate; when the thermal decomposition temperature of the fibers is too low, a large number of fibers may have thermally decomposed during the baking process before rolling, resulting in a large number of pores, which are destroyed during the rolling process. In the baking stage after rolling, fewer fibers are thermally decomposed, and since the pores are partially destroyed during the rolling process, closed pores are formed, which ultimately reduces the effective pore rate.
[0065] In some embodiments, the fibrous polymer material is wool fiber and / or polyvinyl chloride fiber.
[0066] The two types of fibers selected in this application have a suitable thermal decomposition temperature, so that most of the fibers do not undergo thermal decomposition during the baking process before rolling, and the fibers can be thermally decomposed in large quantities or completely during the baking process after rolling, thereby generating as many pores as possible, and the thermal decomposition produces gas escape to avoid the destruction of the pores; the fiber is easy to obtain and has low cost. In addition to the above two materials, other materials whose thermal decomposition temperatures and baking temperatures before and after rolling meet the above relationship can also be selected.
[0067] In some embodiments, the ratio of the fiber length of the fibrous polymer material to the thickness of the active coating of the pole piece is (0.5-1.2):1; for example, the ratio is any value among 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or any range between two values.
[0068] For example, the thickness of the active material layer of the pole piece is 60 to 85 μm; for example, the fiber length of the fibrous polymer material is 40 to 100 μm; further, 60 to 90 μm.
[0069] The specific fiber length of the present application is selected according to the thickness of the electrode. When the fiber length is similar to the thickness of the electrode active coating, the fiber can penetrate the active coating, and after thermal decomposition, a through channel is generated in the active coating, so that the electrolyte entering the channel can infiltrate the bottom of the electrode. The method of adding fibers with a specific thermal decomposition temperature to the slurry of the present application is more suitable for making holes in thick electrodes and has better effects.
[0070] In some embodiments, the molecular weight of the fibrous polymer material is 4W-6W g / mol.
[0071] The fiber molecular weight selected in the present application is related to the thermal decomposition temperature. The higher the molecular weight, the higher the thermal decomposition temperature. The selected fiber molecular weight matches the drying temperature before and after the pole piece rolling, and the fiber decomposition can be achieved at a conventional drying temperature.
[0072] In some embodiments, the fiber diameter of the fibrous polymer material is 60 to 140 μm; further 100 to 120 μm.
[0073] The fiber diameter selected in this application is based on considerations of wettability and process. If the diameter is too small, the pores will be too fine, making it difficult for the electrolyte to enter. If the diameter is too large, obvious defects will occur on the electrode during the coating and drying process. At this diameter and length, the electrode process and electrochemical performance are better.
[0074] In some embodiments, the weight proportion of the fibrous polymer material in the electrode slurry is 0.5% to 5%; 1% to 4%; further 1% to 3%; further 1% to 2%; for example 1.5%.
[0075] In some embodiments, the weight proportion of active material in the electrode slurry is 93% to 97%; the weight proportion of binder in the electrode slurry is 1% to 1.5%; the weight proportion of conductive agent in the electrode slurry is 1% to 1.5%.
[0076] The present application controls the proportion of fiber in the slurry to 1% to 4%, which ensures that a preset amount of pores can be formed without affecting the electrochemical properties of the electrolyte itself; if the fiber content is too high, it will occupy the space of the main material and reduce the energy density of the battery. At the same time, the dispersion process will be difficult, and the dispersion effect in the electrode will be poor, resulting in a decrease in the electrical performance of the battery cell; if the fiber content is too low, there will be no obvious improvement effect on the porosity (electrochemical performance).
[0077] In some embodiments, the electrode sheet is a positive electrode sheet or a negative electrode sheet; the active material is a positive electrode active material or a negative electrode active material.
[0078] The fiber of the present application can be added to the negative electrode slurry or the positive electrode slurry, can be well mixed with the active material and does not affect the properties of the slurry itself; in addition to the above, other conventional materials can also be selected for the positive electrode active material and the negative electrode active material of the present application.
[0079] In some embodiments, the positive electrode active material is selected from lithium cobalt oxide or ternary materials; the negative electrode active material is selected from graphite; the conductive agent is selected from conductive carbon black and / or carbon nanotubes; and the binder is selected from polyvinylidene fluoride.
[0080] The above-mentioned fibers selected in this application can be well mixed with active materials, binders, and conductive agents without affecting the normal functions of these components. Conductive agents and binders can also be selected from other conventional materials.
[0081] According to a second aspect of the present application, a method for preparing an electrode is provided, the method comprising: coating an electrode slurry on a surface of a current collector, and sequentially performing a first baking, rolling and a second baking to obtain an electrode.
[0082] The first baking temperature and the second baking temperature of the present application must match the selected thermal decomposition temperature of the fiber. The first baking temperature cannot be higher than the thermal decomposition temperature of the fiber within a certain range, and the second baking temperature cannot be lower than the thermal decomposition temperature of the fiber. In this way, the fiber will not be thermally decomposed as much as possible during the first baking process, but will be thermally decomposed as much as possible during the second baking process after rolling, thereby generating a large number of effective pores.
[0083] In some embodiments, the temperature of the first baking is 100°C to 130°C; further, 110°C to 130°C; the temperature of the second baking is 150°C to 160°C; further, the temperature of the second baking is 155°C to 160°C.
[0084] The present application adopts the above-mentioned first baking temperature and second baking temperature, and matches the selected fiber thermal decomposition temperature. The first baking temperature is lower than the fiber thermal decomposition temperature or slightly lower than the fiber thermal decomposition temperature, and the fiber thermal decomposition temperature is less than or equal to the second baking temperature; for example, the first baking temperature is selected from any value of 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C or any range between the two; the second baking temperature is selected from any value of 150°C, 155°C, 160°C or any range between the two. When controlling the second baking temperature, the present application also needs to consider that the temperature cannot be too high to destroy the performance of the active material of the electrode sheet.
[0085] In some embodiments, the first baking time is 1-2 hours, the second baking time is 6-10 hours, and the rolling pressure speed is 10-20 m / min, for example, 15 m / min. The above baking time can be adjusted according to the properties of the active coating.
[0086] In some embodiments, the mixing process of the electrode slurry includes: mixing the active material, the conductive agent, the binder and the solvent, adding the fibrous polymer material, mixing and stirring to obtain the electrode slurry; the stirring time is 3 to 5 hours.
[0087] According to a third aspect of the present application, an electrode is provided, which is prepared using the above-mentioned preparation method.
[0088] In some embodiments, the electrode is a positive electrode sheet or a negative electrode sheet; the surface density of the positive electrode sheet is 110-120 g / m 2 ; The surface density of the negative electrode is 60-70g / m 2 .
[0089] The present application adopts a pole piece prepared by a slurry containing a certain amount of specific fibers, which contains a suitable amount of pores, is conducive to absorbing electrolyte for ion exchange, and is conducive to improving the electrochemical performance of the battery.
[0090] The present application adds a small amount of thermally decomposed fibrous polymer material during the homogenization process, and does not use additional pore-making equipment. The process is simple and easy to operate, and the proportion of through holes in the porosity of the electrode can be increased. The pore-making method used in the present application will not damage the electrode structure and will not cause structural failure in the pore-making area.
[0091] According to a fourth aspect of the present application, a battery is provided, comprising the above-mentioned electrode.
[0092] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0093] The raw materials used in the examples of this application are all commercially available.
[0094] The abbreviations of the raw materials used in the examples of this application are explained as follows:
[0095] SP: conductive carbon black; CNT: carbon nanotube; PVDF: polyvinylidene fluoride; NMP: N-methylpyrrolidone.
[0096] Example 1
[0097] Prepare battery positive electrode slurry: add materials according to the mass ratio of LiCoO2:SP:CNT:PVDF:wool fiber = 96%:1%:0.5%:1.3%:1.2%; the wool molecular weight is 4W-5W g / mol, the diameter is 80-120 μm, the length is 40-80 μm, and the thermal decomposition temperature is 130-160°C;
[0098] (1) firstly, mixing lithium cobalt oxide and conductive carbon black uniformly to form a mixture;
[0099] (2) dissolving PVDF in NMP to prepare a gel solution with a solid content of 5%;
[0100] (3) mixing the mixture in step (1) and the glue in step (2) to obtain a mixed solution;
[0101] (4) mixing the mixed solution in step (3) and carbon nanotubes (3 wt %) uniformly to obtain a mixed slurry;
[0102] (5) The mixed slurry in step (4) and the wool fiber were mixed and stirred at 25 rpm for 4 h to obtain a positive electrode slurry;
[0103] Preparation of positive electrode sheet:
[0104] The slurry was coated on a 9 μm thick aluminum foil, and the coated aluminum foil was baked in an oven at 120° C. for the first time, and then cold pressed to obtain a positive electrode sheet (such as Figure 1 The rolled positive electrode sheet was baked for a second time at 165°C for 8 hours (as shown in Figure 2 After drying, the density is 118g / m 2 , the cold pressing speed is 15m / min.
[0105] Example 2
[0106] Prepare battery positive electrode slurry: add materials according to the mass ratio of LiCoO2:SP:CNT:PVDF:polyvinyl chloride = 96%:1%:0.5%:1.3%:1.2%; the molecular weight of polyvinyl chloride is 4W-6Wg / mol, the diameter is 100-120μm, the length is 60-100μm, and the thermal decomposition temperature is 130-160°C;
[0107] (1) firstly, mixing lithium cobalt oxide and conductive carbon black uniformly to form a mixture;
[0108] (2) dissolving PVDF in NMP to prepare a gel solution with a solid content of 5%;
[0109] (3) mixing the mixture in step (1) and the glue in step (2) to obtain a mixed solution;
[0110] (4) mixing the mixed solution in step (3) and carbon nanotubes (3 wt %) uniformly to obtain a mixed slurry;
[0111] (5) The mixed slurry described in step (4) and polyvinyl chloride were mixed and stirred at 25 rpm for 4 hours to obtain a positive electrode slurry.
[0112] The positive electrode preparation method is as follows:
[0113] The slurry was coated on a 9μm thick aluminum foil, dried in an oven at 125°C for the first time, and cold pressed to obtain a positive electrode sheet. The rolled positive electrode sheet was baked for a second time at 160°C for 8 hours. The density after drying was 118g / m 2 , the cold pressing speed is 15m / min.
[0114] Example 3
[0115] Prepare the battery negative electrode slurry: add materials according to the mass ratio of graphite: SP: CNT: SBR: wool fiber = 96.5%: 0.5%: 0.5%: 1.3%: 1.2%; the wool molecular weight is 4W-5W g / mol, the diameter is 80-120 μm, the length is 40-80 μm, and the thermal decomposition temperature is 130-160°C;
[0116] (1) firstly, graphite and conductive carbon black are mixed uniformly to form a mixture;
[0117] (2) dissolving the mixture in (1) in water, and adding water at a solid content of 70%;
[0118] (3) mixing the mixed solution in (2) and carbon nanotubes (6 wt %) uniformly;
[0119] (4) The mixed slurry in (3) and wool fiber were mixed and stirred at 25 rpm for 4 h, and then SBR was added and stirred to obtain a negative electrode slurry.
[0120] The negative electrode sheet preparation method is as follows:
[0121] The slurry was coated on a 6μm thick copper foil, baked in an oven at 123°C for the first time, and then cold pressed to obtain a negative electrode sheet. The rolled negative electrode sheet was baked for a second time at 163°C for 8 hours. The density of the negative electrode sheet after drying was 65g / m 2 , the cold pressing speed is 25m / min.
[0122] Example 4
[0123] Prepare the negative electrode slurry of the battery: add materials according to the mass ratio of graphite: SP: CNT: SBR: polyvinyl chloride = 96.5%: 0.5%: 0.5%: 1.3%: 1.2%; the molecular weight of polyvinyl chloride is 4W-6Wg / mol, the diameter is 100-120μm, the length is 60-100μm, and the thermal decomposition temperature is 130-160°C;
[0124] (1) firstly, graphite and conductive carbon black are mixed uniformly to form a mixture;
[0125] (2) dissolving the mixture in (1) in water, and adding water at a solid content of 70%;
[0126] (3) mixing the mixed solution in (2) and carbon nanotubes (6 wt %) uniformly;
[0127] (4) The mixed slurry in (3) and polyvinyl chloride were mixed and stirred at 25 rpm for 4 h, and then SBR was added to obtain a negative electrode slurry.
[0128] The negative electrode sheet preparation method is as follows:
[0129] The slurry was coated on a 6μm thick copper foil, baked in an oven at 128°C for the first time, and cold pressed to obtain a negative electrode sheet. The rolled negative electrode sheet was baked for a second time at 161°C for 8 hours. The surface density of the negative electrode sheet is 65g / m 2 , the cold pressing speed is 25m / min.
[0130] Example 5
[0131] The difference between Example 5 and Example 1 is that the first baking temperature before rolling is 100°C, and the second baking temperature after rolling is 165°C.
[0132] Example 6
[0133] The difference between Example 6 and Example 1 is that the first baking temperature before rolling is 110°C, and the second baking temperature after rolling is 160°C.
[0134] Example 7
[0135] The difference between Example 7 and Example 2 is that the first baking temperature before rolling is 105°C, and the second baking temperature after rolling is 163°C.
[0136] Example 8
[0137] The difference between Example 8 and Example 2 is that the first baking temperature before rolling is 115°C, and the second baking temperature after rolling is 160°C.
[0138] Example 9
[0139] The difference between Example 9 and Example 1 is that the mass addition ratio of wool in the positive electrode slurry is 2%.
[0140] Example 10
[0141] The difference between Example 10 and Example 1 is that the mass addition ratio of wool in the positive electrode slurry is 3%.
[0142] Embodiment 11
[0143] The difference between Example 11 and Example 1 is that the mass addition ratio of wool and polyvinyl chloride in the positive electrode slurry is 2% each.
[0144] Example 12
[0145] The difference between Example 12 and Example 1 is that the mass addition ratio of wool in the positive electrode slurry is 0.5%.
[0146] Embodiment 13
[0147] The difference between Example 13 and Example 1 is that the mass addition ratio of wool in the positive electrode slurry is 5%.
[0148] Comparative Example 1
[0149] The difference between Comparative Example 1 and Example 1 is that the first baking temperature is 130°C.
[0150] Comparative Example 2
[0151] The difference between Comparative Example 2 and Example 1 is that the second baking temperature is 130°C.
[0152] Comparative Example 3
[0153] The difference between Comparative Example 3 and Example 3 is that no polymer fiber is added to the slurry;
[0154] Battery negative electrode slurry: graphite: SP: CNT: SBR = 97.7%: 0.5%: 0.5%: 1.3%;
[0155] (1) firstly, graphite and conductive carbon black are mixed uniformly to form a mixture;
[0156] (2) dissolving the mixture in (1) in water, and adding water at a solid content of 70%;
[0157] (3) The mixed solution in (2) and carbon nanotubes (6 wt%) are evenly mixed, and SBR is added to obtain a negative electrode slurry.
[0158] Comparative Example 4
[0159] The difference between Comparative Example 4 and Example 3 is that ammonium bicarbonate is used as a pore-forming agent;
[0160] Prepare the negative electrode slurry of the battery: graphite: SP: CNT: SBR: ammonium bicarbonate = 96.5%: 0.5%: 0.5%: 1.3%: 1.2% ratio;
[0161] (1) firstly, graphite and conductive carbon black are mixed uniformly to form a mixture;
[0162] (2) dissolving the mixture in (1) in water, and adding water at a solid content of 70%;
[0163] (3) mixing the mixed solution in (2) and the carbon nanotubes uniformly, wherein the mass fraction of the carbon nanotubes is 6%;
[0164] (4) The mixed slurry in (3) and ammonium bicarbonate are mixed and stirred, and then SBR is added to obtain a negative electrode slurry.
[0165] Application Examples
[0166] The positive electrode sheets prepared in the examples and comparative examples were respectively assembled with conventional negative electrode sheets without polymer fibers, ceramic glue-coated separators (base film thickness 5 μm, double-sided ceramic, ceramic thickness 1 μm, double-sided glue coating, glue layer thickness 1 μm), and electrolytes to form batteries with a capacity of 1800 mAh, wherein the electrolyte composition was EC:EMC:PP:LiPF6=25:10:50:15, mass ratio;
[0167] The negative electrode plates prepared in the embodiments and comparative examples were respectively assembled with conventional positive electrode plates without polymer fibers, ceramic coated separators (base film thickness 5 μm, double-sided ceramic, ceramic thickness 1 μm, double-sided glue coating, glue layer thickness 1 μm), and electrolytes into batteries with a capacity of 1800 mAh; wherein the electrolyte composition is EC:EMC:PP:LiPF6=25:10:50:15, mass ratio); and the electrochemical properties of the above batteries were tested respectively.
[0168] Electrolyte absorption rate test method: Cut the rolled electrode sheets of each embodiment and comparative example into equal-sized pieces with an area of 1600 mm 2 , weigh and record m0; then soak the rolled electrodes in the electrolyte (EC:EMC:PP:LiPF6=25:10:50:15, mass ratio) for 4 hours, take them out, air-dry for 30 seconds, weigh and record as m2, the liquid absorption rate is (m1-m0) / m0, the test results are shown in Table 1.
[0169] Electrochemical performance test conditions: The battery composed of the rolled electrode sheets of each embodiment and comparative example was charged at a temperature of 25°C and a rate of 1C, and the rate discharge performance test was performed under the conditions of 1C / 3A / 7A / 10A; the test results are shown in Table 2.
[0170] Table 1
[0171] sample Liquid absorption rate (%) Example 1 30 Example 2 21 Example 3 25 Example 4 18 Example 5 31 Example 6 30 Example 7 20 Example 8 23 Example 9 33 Example 10 35 Embodiment 11 34 Example 12 9 Embodiment 13 38 Comparative Example 1 12 Comparative Example 2 10 Comparative Example 3 8 Comparative Example 4 13
[0172] Table 2
[0173]
[0174]
[0175] The test results in Table 1 show that the liquid absorption rate of the electrode sheets prepared in Examples 1 to 13 of the present application in the electrolyte reaches 9% to 38%, most of which are concentrated above 20, or even above 25; the liquid absorption rate of the electrode sheets prepared in Comparative Examples 1 and 2 reaches 10% to 12%; among them, the liquid absorption rate of Comparative Example 1 is 12%, and the first baking temperature before rolling is too high. The coating baking temperature is too high, which will cause the electrode sheet to crack. At the same time, the fiber decomposition temperature is higher than the fiber decomposition temperature, which will cause the fiber to decompose before rolling and form pores. After rolling, the pores are destroyed into closed pores. The remaining fibers form fewer pores during the second baking process, and the effective pore rate of the electrode sheet is reduced, resulting in a significant reduction in its liquid absorption. Among them, the liquid absorption rate of Comparative Example 2 is 10%, and the second baking temperature is too low, lower than the fiber thermal decomposition temperature. After rolling, the fiber thermal decomposition rate in the electrode sheet is reduced, and a sufficient number of pores are not formed, resulting in a significant reduction in the amount of washing liquid.
[0176] Among them, in Comparative Example 3, no pore-forming agent was added to the slurry, and the liquid absorption rate of the electrode sheet reached 8%. In Comparative Example 4, ammonium bicarbonate was used as a pore-forming agent, and the liquid absorption rate of the electrode sheet reached 13%. By comparison, it can be seen that the liquid absorption of the electrode sheet in the present application in which specific fibers are added to the slurry is mostly about 1.5 to 2.5 times the liquid absorption of the traditional electrode sheet in which ammonium bicarbonate pore-forming agent is added to the slurry, and is about 2.3 to 4 times the liquid absorption of the traditional electrode sheet in which no pore-forming agent is added to the slurry; it is obvious that the present application can significantly improve the liquid absorption rate of the electrode sheet by adding specific fibers to the slurry, thereby improving the electrochemical performance of the battery.
[0177] The test results in Table 2 show that the battery assembled with the electrode sheets prepared in Examples 1 to 13 in this application is discharged at a rate of 1C / 3A / 7A / 10A, and the capacity retention rates are 100%, 97.00% to 99.80%, 95.4% to 97.50%, and 91.20% to 95.60% respectively. The capacity retention rates of Comparative Examples 1 to 4 are 100%, 97.00% to 98.6%, 94.8% to 95.9%, and 91.0% to 92.8% respectively. The 3A, 7A, and 10A rate capacity retention rates of the battery composed of the electrode sheets in this application in which specific fibers are added to the slurry are obviously better than those of Comparative Examples 1 to 4 in most cases, which significantly improves the battery capacity retention rate.
[0178] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0179] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An electrode slurry, characterized in that: The electrode slurry includes an active material, a binder and a conductive agent; a fibrous polymer material is also added to the electrode slurry; the thermal decomposition temperature T of the fibrous polymer material, the baking temperature T1 of the electrode sheet coated with the electrode slurry before rolling, and the baking temperature T2 after rolling satisfy the following relationship: T1<T≤T2.
2. The electrode slurry according to claim 1, characterized in that: The relationship is: T1+10°C≤T≤T2; preferably: T1+20°C≤T≤T2; further preferably: T1+30°C≤T≤T2.
3. The electrode slurry according to claim 1 or 2, characterized in that: The T1 is 100-130°C; preferably, the T1 is 110-130°C; And / or, the T is 120-160°C; preferably, the T is 130-160°C; further preferably, the T is 140-160°C; And / or, the T2 is 150-165°C; preferably, the T2 is 160-165°C.
4. The electrode slurry according to any one of claims 1 to 3, characterized in that: The fibrous polymer material is wool fiber and / or polyvinyl chloride fiber; And / or, the ratio of the fiber length of the fibrous polymer material to the thickness of the active coating of the pole piece is (0.5-1.2):
1.
5. The electrode slurry according to any one of claims 1 to 4, characterized in that: The molecular weight of the fibrous polymer material is 4W to 6W g / mol; And / or, the thickness of the active material layer of the pole piece is 60 to 85 μm; And / or, the fiber length of the fibrous polymer material is 40 to 100 μm; preferably 60 to 90 μm; And / or, the fiber diameter of the fibrous polymer material is 60 to 140 μm, preferably 100 to 120 μm.
6. The electrode slurry according to any one of claims 1 to 5, characterized in that: The weight proportion of the fibrous polymer material in the electrode slurry is 0.5% to 5%; preferably 1% to 4%; more preferably 1% to 3%; and further preferably 1% to 2%. And / or, the weight proportion of active material in the electrode slurry is 93% to 97%; the weight proportion of binder in the electrode slurry is 1% to 1.5%; the weight proportion of conductive agent in the electrode slurry is 1% to 1.5%; And / or, the electrode is a positive electrode or a negative electrode; and / or, the active material is a positive electrode active material or a negative electrode active material; Preferably, the positive electrode active material is selected from lithium cobalt oxide or ternary materials; Preferably, the negative electrode active material is selected from graphite; Preferably, the conductive agent is selected from conductive carbon black and / or carbon nanotubes; Preferably, the binder is selected from polyvinylidene fluoride.
7. A method for preparing an electrode, characterized in that: The method comprises: coating the electrode slurry on the surface of the current collector, and sequentially performing a first baking, rolling and a second baking to obtain the electrode; Wherein, the electrode slurry is the electrode slurry according to any one of claims 1 to 6.
8. The method for preparing an electrode according to claim 7, characterized in that: The temperature of the first baking is 100°C to 130°C, preferably 110°C to 130°C; And / or, the temperature of the second baking is 150°C to 165°C; preferably 160°C to 165°C; And / or, the first baking time is 1 to 2 hours; And / or, the second baking time is 6 to 10 hours; And / or, the rolling pressure speed is 10 to 20 m / min; And / or, the mixing process of the electrode slurry includes: mixing the active material, the conductive agent, the binder and the solvent, adding the fibrous polymer material, mixing and stirring to obtain the electrode slurry; preferably, the stirring time is 3 to 5 hours.
9. An electrode, characterized in that: The electrode is prepared by the method for preparing the electrode according to claim 7 or 8; Preferably, the electrode is a positive electrode sheet or a negative electrode sheet; the surface density of the positive electrode sheet is 110-120 g / m 2 The surface density of the negative electrode sheet is 60-70 g / m 2 .
10. A battery comprising an electrode; characterized in that: The electrode is the electrode according to claim 9.
Citation Information
Patent Citations
Method for preparing panel SOFC (Solid Oxide Fuel Cell) anode by using natural fibre as pore-forming agent
CN102347493A
Silicon-carbon composite material and preparation method thereof
CN102709536A
Preparation method of lithium iron phosphate pole piece, and lithium ion battery
CN113972373A
Electrode plate, preparation method thereof and lithium ion battery
CN119092636A
Electrode plate, preparation method thereof and battery
CN119092643A
Cited By
Electrode slurry, electrode and preparation method therefor, and battery
WO2026137965A1